2014
DOI: 10.1007/s00417-014-2851-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-year corneal graft survival rate in high-risk cases treated with subconjunctival and topical bevacizumab

Abstract: Combined subconjunctival and topical bevacizumab treatment may improve corneal graft survival rate in the majority of high-risk cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Furthermore, Fasciani et al 51 showed the safety and efficacy of preoperative treatment of corneal neovascularization with bevacizumab before HR keratoplasty. Dekaris et al 44 also found that 70% of HR grafts remained clear during 3 years of follow-up after combined subconjunctival and topical bevacizumab treatment.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 92%
“…Furthermore, Fasciani et al 51 showed the safety and efficacy of preoperative treatment of corneal neovascularization with bevacizumab before HR keratoplasty. Dekaris et al 44 also found that 70% of HR grafts remained clear during 3 years of follow-up after combined subconjunctival and topical bevacizumab treatment.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 92%
“…Just recently, we demonstrated that the fine-needle diathermy in combination with subconjunctival injection of Bevacizumab prior to high-risk keratoplasty in patients results in graft survival rates comparable to survival rates seen in normal-risk keratoplasty [63]. Moreover, a combined subconjunctival and topical Bevacizumab treatment improves the graft survival rate in 70% of high-risk transplantations during three years of follow-up [60].…”
Section: Endogenous Regulators Of Lymphangiogenesis In Corneal Transpmentioning
confidence: 81%
“…This approach has been transferred to the clinic and several studies have shown promising results following Bevacizumab treatment for corneal neovascularization in patients before and/or after penetrating keratoplasty. So, it could be shown that intrastromal application [56][57][58], topical application [59][60][61] and subconjunctival injection [62] respectively of Bevacizumab leads to a reduction in corneal neovascularization and so enables long term success of subsequent corneal transplantation after high-risk transplantation. Just recently, we demonstrated that the fine-needle diathermy in combination with subconjunctival injection of Bevacizumab prior to high-risk keratoplasty in patients results in graft survival rates comparable to survival rates seen in normal-risk keratoplasty [63].…”
Section: Endogenous Regulators Of Lymphangiogenesis In Corneal Transpmentioning
confidence: 99%
“…Furthermore, meta-analysis of human clinical studies revealed that the corneal neovascularization area attenuated by 32% after subconjunctival injection, 48% after topical treatment and 36% overall following anti-VEGF administration [96•]. Thus, simultaneous administration of topical and subconjunctival bevacizumab might result in better corneal graft survival rate in most of high-risk patients [88]. In several animal studies application of topical and subconjunctival ranibizumab caused regression of corneal neovascularization and prevented graft rejection [97100].…”
Section: Experimental Approachesmentioning
confidence: 99%